Innovative production machines and systems : fifth I*PROMS Virtual Conference, 6-17th July 2009 - Pham, D. T.; Eldukhri, E. E.; Soroka, A. J. (Whittles, 2010)
This collection of almost 70 papers is a focal point for access to information from researchers and industrial practitioners in the field of intelligent systems and soft computing techniques and their application in diverse areas within manufacturing.
Conference proceedings.
Keywords: Automatic control -- Congresses.; CAD/CAM systems -- Congresses.; elektronické knihy; electronic books